2015
DOI: 10.1037/pag0000054
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of depressive symptoms in old age: Integrating age-, pathology-, and mortality-related changes.

Abstract: Late life involves a variety of different challenges to well-being. This study extends upon and qualifies propositions drawn from the paradox of well-being in aging using 15-year longitudinal data on depressive symptoms from old and very old participants in the Australian Longitudinal Study of Ageing (at baseline n = 2,087, M age = 78.69 years, range = 65-103 years; 49.40% women). We first examined age-related trajectories in depressive symptoms from young-old to oldest-old, taking into account (changes in) re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 95 publications
(208 reference statements)
2
19
1
2
Order By: Relevance
“…Here also, this finding is in line with late-life depression literature (Zhang et al, 2009). For instance, Chui et al (2015) found that depressive symptoms increase from the young old to the oldest old. To summarize, our results revealed that the GDS 15 scores reflected a relatively stable and enduring trait explaining between-person differences in depressivity in our sample.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Here also, this finding is in line with late-life depression literature (Zhang et al, 2009). For instance, Chui et al (2015) found that depressive symptoms increase from the young old to the oldest old. To summarize, our results revealed that the GDS 15 scores reflected a relatively stable and enduring trait explaining between-person differences in depressivity in our sample.…”
Section: Discussionsupporting
confidence: 89%
“…For instance, Chui et al . () found that depressive symptoms increase from the young old to the oldest old.…”
Section: Discussionmentioning
confidence: 97%
“…Esse resultado evidencia que a prevalência de sintomatologia depressiva, em geral, tende a ser superior em idosos quando comparados a adultos 53,54 . De acordo com o estudo de revisão sistemática e metanálise realizada para adultos brasileiros por Silva et al 15 , a prevalência de sintomatologia depressiva foi de 14,0% (IC de 95%: 13,0-16,0).…”
Section: Discussionunclassified
“…We used a shared parameter growth-survival model (Chui et al, 2015; Ghisletta, 2008; Ghisletta, McArdle, & Lindenberger, 2006; Infurna et al, 2013; Infurna & Okun, 2015; Muniz-Terrera, Piccinin, Johansson, Matthews, & Hofer, 2011; Sabia et al, 2014; Sargent-Cox, Anstey, & Luscz, 2014) to examine links between trajectories of life satisfaction and mortality. A graphical illustration of the model can be found in Figure 1.…”
Section: Methodsmentioning
confidence: 99%